ANALYSIS OF THE SCOPE AND RULE OF TJARRI (EFFRONTERY) IN IMAMIA JURISPRUDENCE AND ITS APPLICATION TO INCOMPLETE CRIMES Ø¯ÙˆØ±Ù‡51 Ø´Ù…Ø§Ø±Ù‡3 Ø³Ø§Ù„1398 - ??? ?????, ???????????; ?? ??, ??? ???? (??? ? ????)
One of the deficiencies of the Iranian penal law is the failure to pay enough attention to the issue of tajarri (effrontery); despite disagreement among Islamic jurists regarding tajarri, undoubtedly, if tajarri is against public interests and other persons' rights and the dangerous status of the person committing effrontery (motajarri) is identified, a discretionary punishment may be executed on him or he may be sentenced to security measures  at the Islamic judge?s discretion , in order to prevent commitment of crime. However, such issue has not been envisaged by the legislator. The second point neglected in this regard is the failure to offer the exact definition and scope of tajarri; based on the famous definition of tajarri, its scope is limited to the case where an individual, based on his definite belief, violates practically, the divine lawgiver?s obligatory verdict, but subsequently, it becomes clear that the committed act was permitted. But it is understood from the statements of some Islamic jurists that any case of practical violation of the lawgiver's obligatory verdict in which the perpetrator does not achieve his purpose, is considered as tajarri, accordingly, a new definition of tajarri may be given which extends its scope to incomplete crimes as well. The authors, in this paper, intend, in addition to explaining different opinions of Islamic jurists concerning the scope of tajarri, to emphasize on its broad definition and clarify its status in penal law. Likewise, the authors intend to study in summary the origin of controversy among Usulis and strengthen the prohibition of tajarri on the basis of secondary verdict.